A Study of Factors Influencing VCT Service Utilization among the Youths: A Case Study of Kapsabet Division, Nandi County, Kenya - Ndwiga, Taratisio; Omwono, Masta (Scientific Research, 2014)
Voluntary Counseling and Testing (VCT) is important in controlling the spread of HIV/AIDS especially among the Youths. The aim of the study was to determine the extent, to assess the level of awareness and to describe the Youths’ attitude towards VCT Service Utilization in Kapsabet Division, Nandi Central District from 1st February to 30th April 2013. A cross-sectional descriptive study was carried out among male and female Youths aged 18 - 34 years who were selected by convenience sampling, using Quantitative and Qualitative methods of data collection with mean age of 26 years. The study found that 52% of Youths had visited VCT and the majority was aware about VCT through print media, TV/radio and IEC materials. Forth-six percent (46%) said Post-Counseling was poor. Seventy seven (77%) highlighted various challenges i.e. most VCT centers were openly located within the hospital and user fee Ksh. 20 was charged. The study also found that there was high level of awareness but slightly low utilization of VCT Services with only 52% having tested. Posters in VCT rooms were stigmatizing and this could have influenced their low utilization of VCT Services. Therefore there is need for dialogue with policy-makers, Youths and Stakeholders in regards to changing strategy for future efforts to increase the uptake of services among the Youths.
Keywords: Voluntary Testing and Counseling; Discrimination; Stigma; Youth; Service Providers